PENGARUH REWARD DAN PERSEPSI PEKERJAAN TERHADAP KOMITMEN MENGAJAR GURU - SUHARDI, MUHAMAD (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research is made to determine (1) the influence between reward on perception of task teacher of state senior high school, (2) the influence between reward on organization commitment teacher of state senior high school, and (3) ) the influence between perception of task on organization commitment teacher of state senior high school. The research methodology that has been used was survey with path analysis technique in testing hypothesis. In this study, 96 teacher of state senior high school have been used as a sample by using simple random sampling techniques (simple random sampling). Based on the description of hypothesis test, the researches findings can be outlined as followed: (1) there is a positive direct effect of reward on perception of task; (2) there is a positive direct effect of reward on organization commitment; and (3) there is a positive direct effect of perception of task on organization commitment. The implication of this study is attempt of improving the organization commitment teacher of state senior high school that can be done through improve reward and perception of task. ABSTRAKPenelitian ini dilakukan untuk mengetahui (1) pengaruh antara reward terhadap persepsi tugas guru SMA Negeri, (2) pengaruh antara reward terhadap komitmen organisasi guru SMA Negeri, dan (3) ) pengaruh antara persepsi tugas komitmen organisasi guru sekolah menengah atas negeri. Metodologi penelitian yang digunakan adalah survei dengan teknik analisis jalur dalam menguji hipotesis. Dalam penelitian ini, guru SMA Negeri yang berjumlah 96 orang dijadikan sampel dengan menggunakan teknik pengambilan sampel acak sederhana (simple random sampling). Berdasarkan uraian uji hipotesis, maka temuan penelitian dapat diuraikan sebagai berikut: (1) terdapat pengaruh langsung positif reward terhadap persepsi tugas; (2) terdapat pengaruh langsung positif reward terhadap komitmen organisasi; dan (3) terdapat pengaruh langsung positif persepsi tugas terhadap komitmen organisasi. Implikasi dari penelitian ini adalah upaya meningkatkan komitmen organisasi guru SMA Negeri yang dapat dilakukan melalui peningkatan penghargaan dan persepsi terhadap tugas.